Integration of problem-based learning with digital technology in science learning for critical thinking skills - Intan Yonsyah Intan; Asri Widowati (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
This study investigates the integration of Problem-Based Learning (PBL) with digital technology in science education and its potential to enhance students’ critical thinking skills in the 21st century. Using a systematic literature review, 28 studies published between 2005 and 2025 were analyzed through thematic analysis. The review shows a steady growth of research on digital PBL, demonstrating its effectiveness in promoting critical thinking, problem-solving, and creativity. Supporting factors include adequate digital infrastructure, school and teacher support, while barriers such as the digital divide, limited training, and cognitive overload remain challenges. Despite its promise, existing studies rarely adopt longitudinal designs and often lack standardized instruments for measuring critical thinking. The findings highlight that integrating Digital PBL offers a transformative approach to science learning, enabling more interactive and inclusive classrooms. Theoretically, this study reinforces constructivist perspectives by showing how digital PBL fosters active knowledge construction. Practically, it provides insights for policymakers and educators to strengthen teacher training, improve infrastructure, and design more robust frameworks for sustainable digital PBL implementation.